Actuator characterisations to achieve approximate controllability for a class of fractional sub-diffusion equations. Issue 6 (3rd June 2017) - Ge, Fudong; Chen, YangQuan; Kou, Chunhai
ABSTRACT: This paper is devoted to analysing the actuator characterisations for the fractional sub-diffusion equation under consideration to become approximately controllable. Two different cases are considered, where the control inputs emerge in the differential equation as distributed inputs and as boundary inputs in the boundary conditions. The dual system for fractional sub-diffusion equation is solved and the necessary and sufficient conditions for the approximate controllability of the system are established. Several examples are worked out in the end to illustrate our results.